THE RELATIONSHIP BETWEEN PUBLIC SECTOR INTERNAL CONTROLS AND FRAUD PREVENTION - Alend Talla; Shella Gilby Sapulette; Franco Benony Limba (Adisam Publisher, 2025)
This study examines the relationship between public sector internal controls and fraud prevention by employing a literature review method. Internal control systems serve as an essential mechanism to safeguard public resources, ensure accountability, and uphold transparency in government financial management. A well-structured internal control framework, which includes preventive, detective, and corrective mechanisms, plays a critical role in mitigating fraud risks by reducing opportunities for misconduct. Through a comprehensive analysis of previous studies, this research highlights that effective internal controls such as segregation of duties, monitoring, risk assessment, and ethical leadership significantly contribute to the reduction of fraudulent practices in the public sector. Furthermore, the findings suggest that the success of fraud prevention efforts is not solely determined by formal control mechanisms, but also by the integrity, competence, and commitment of public officials in enforcing these controls. The study concludes that strengthening internal control systems in the public sector is vital for enhancing good governance and preventing corruption.